2020
DOI: 10.1111/nph.16732
|View full text |Cite|
|
Sign up to set email alerts
|

PIFs coordinate shade avoidance by inhibiting auxin repressor ARF18 and metabolic regulator QQS

Abstract: Shade avoidance syndrome (SAS) arises in densely growing plants that compete for light. In Arabidopsis thaliana, phytochrome interacting factor (PIF) proteins link the perception of shade to stem elongation via auxin production. Here, we report that PIFs inhibit the shade-induced expression of AUXIN RESPONSE FACTOR 18 (ARF18), and ARF18 represses auxin signaling. Therefore, PIF-mediated inhibition of ARF18 enhances auxin-dependent hypocotyl elongation in simulated shade. Furthermore, we show that both PIFs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…This is a highly complex network, and this complexity is further increased by the fact that within the ARF family (Roosjen et al, 2017) there are both auxin repressors and activators. A recent study, for example, identified how PIFs inhibit the expression of ARF18, which encodes a transcription factor that inhibits auxin signaling (Jia et al, 2020), whereas other ARFs promote auxin signaling and growth (Reed et al, 2018). Active phyB and cry1 have also been proposed to directly interact with auxin signaling-promoting ARF proteins, such as ARF6 and ARF8, to repress their DNA binding ability (Mao et al, 2020), as well as with specific AUX/IAA proteins where photoreceptor interaction stabilizes AUX/IAAs (Xu et al, 2018).…”
Section: Auxinmentioning
confidence: 99%
“…This is a highly complex network, and this complexity is further increased by the fact that within the ARF family (Roosjen et al, 2017) there are both auxin repressors and activators. A recent study, for example, identified how PIFs inhibit the expression of ARF18, which encodes a transcription factor that inhibits auxin signaling (Jia et al, 2020), whereas other ARFs promote auxin signaling and growth (Reed et al, 2018). Active phyB and cry1 have also been proposed to directly interact with auxin signaling-promoting ARF proteins, such as ARF6 and ARF8, to repress their DNA binding ability (Mao et al, 2020), as well as with specific AUX/IAA proteins where photoreceptor interaction stabilizes AUX/IAAs (Xu et al, 2018).…”
Section: Auxinmentioning
confidence: 99%
“…Besides the vital role in photomorphogenesis, PIFs are also involved in the regulation of many other cellular processes, including fruit ripening, flowering time, and hormone response ( Paik et al, 2017 ). For example, Arabidopsis PIFs have important functions in shade avoidance response (SAS) mainly through auxin biosynthesis and auxin signaling ( Hornitschek et al, 2012 ; Hersch et al, 2014 ; Pacín et al, 2016 ; Jia et al, 2020 ), as well as via other phytohormones including gibberellin (GA) and brassinosteroid (BR) ( Feng et al, 2008 ; Sorin et al, 2009 ; Xie et al, 2017 ; Hayes et al, 2019 ; Wang X. et al, 2020 ). Additionally, PIF1, PIF3, PIF4, PIF5, and PIF7 are necessary for the phy-mediated seasonal regulation of hypocotyl elongation in Arabidopsis ( Leivar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Photoreceptors directly interact with essential component factors involved in auxin signaling transduction pathway, and two recent studies point out that light can also regulate AUX/IAAs or ARFs by PIFs (Pucciariello et al, 2018; Jia et al, 2020) (Figure 1). Pucciariello et al, (2018) found that prolonged shade‐maintained elevated levels of PIF4 in the hypocotyl directly activate the expression of IAA19 and IAA29 , which in turn reduce the expression of the growth‐repressive IAA17 and abundance of ARF6 to sustain shade avoidance.…”
Section: Light Controls Plant Growth Through Regulating Auxin Signalingmentioning
confidence: 99%
“…Pucciariello et al, (2018) found that prolonged shade‐maintained elevated levels of PIF4 in the hypocotyl directly activate the expression of IAA19 and IAA29 , which in turn reduce the expression of the growth‐repressive IAA17 and abundance of ARF6 to sustain shade avoidance. Jia et al, (2020) showed that PIFs attenuated the shade‐induced up‐regulation of AFR18 , an auxin signaling repressor, to enhance auxin‐dependent hypocotyl elongation in simulated shade.…”
Section: Light Controls Plant Growth Through Regulating Auxin Signalingmentioning
confidence: 99%
See 1 more Smart Citation